Digital communication in a virtual community of practice: Linguistic/paralinguistic behaviour in the multimodal context of Blackboard Collaborate - Chen, Julian; Dobinson, Toni (2020)
Australian university academics have used Blackboard Collaborate (BC), a synchronous, multimodal platform, with online students for some years now. Its role as a promoter or detractor of social presence online and its influence on linguistic/paralinguistic choices still needs investigation, however, if this tool is to be fully utilised. The study reported in this chapter examined tele/co-presence and linguistic/ paralinguistic behaviours in BC sessions. Findings were drawn from a larger mixed-methods study which explored the experiences of students and academics using BC at one Australian university. Framed by notions of virtual community of practice, and social presence theory, the study viewed interaction in the BC session through the lens of student-teacher, student-student communication. It examined distinct linguistic/paralinguistic behaviour fostered by the multimodal nature of BC through the collection of in-depth qualitative data from eleven undergraduate students and seven university academics. Interviews were face-to-face, semi-structured and recorded while the survey utilised open-ended questions. Key themes in the findings were 1) students’ and academics’ different responses to the sense of tele/co-presence shaped by, and shaping, community building in the digital third space; 2) the various, linguistic and paralinguistic choices fostered by the multimodal nature of BC sessions.